2008
DOI: 10.1063/1.2833010
|View full text |Cite
|
Sign up to set email alerts
|

Surface Specularity as an Indicator of Shock-Induced Solid-Liquid Phase Transitions in Tin

Abstract: Abstract. When highly polished metal surfaces melt upon release after shock loading, they exhibit features that suggest significant surface changes accompany the phase transition. The reflection of light from such surfaces changes from specular (pre-shock) to diffuse upon melting. Typical of this phenonmenon is the loss of signal light in velocity interferometer system for any reflector (VISAR) measurements, which usually occurs at pressures high enough to melt the free surface. Unlike many other potential mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The Hugoniot state (the equilibrium state behind the shockwave front) and solid-liquid phase transformations have been extensively studied over the last several decades using molecular dynamics (MD) simulations and experimental methods [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. For example, Bringa et al [3] investigated the Hugoniot state during shock of single crystal copper along several different crystallographic directions for Hugoniot pressures between 2 and 800 GPa and reported that the shock velocity magnitude as a function of particle velocity was anisotropic.…”
Section: Introductionmentioning
confidence: 99%
“…The Hugoniot state (the equilibrium state behind the shockwave front) and solid-liquid phase transformations have been extensively studied over the last several decades using molecular dynamics (MD) simulations and experimental methods [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. For example, Bringa et al [3] investigated the Hugoniot state during shock of single crystal copper along several different crystallographic directions for Hugoniot pressures between 2 and 800 GPa and reported that the shock velocity magnitude as a function of particle velocity was anisotropic.…”
Section: Introductionmentioning
confidence: 99%